Protective effect of N-acetylcysteine on kidney as a remote organ after skeletal muscle ischemia-reperfusion - Takhtfooladi,Mohammad Ashrafzadeh (2012)
PURPOSE: To investigate whether N-acetylcysteine has a protective effect against renal injury as a remote organ after skeletal muscle ischemia-reperfusion in rats. METHODS: Twenty Wistar male rats were divided randomly into two experimental groups: group ischemia-reperfusion (group I) and group ischemia-reperfusion + N-acetylcysteine (group II). After ketamine and xylazine anesthesia, femoral artery was exposed. All animals were undergone 2h of ischemia by occlusion femoral artery and 24h of reperfusion. Rats that were treated with N-acetylcysteine given IV at a dose of 150 mg/kg-¹, immediately before reperfusion. After 24h of reperfusion, the blood samples were collected and submitted for evaluation of plasmatic urea, creatinine values and then rats were euthanized and left kidney harvested for histopathological analysis under light microscopy. RESULTS: The urea (35±7.84 mg.dL-1), creatinine (1.46±0.47 mg.dL-1) values were significantly lower in group II (P=0.000). Renal histopathologic study in group I showed extensive distal and proximal tubular cells necrosis and sloughing of epithelial cells into the tubular lumen, cast formation in tubule and glomerul, glomerul fibrosis and hemorrhage. Histopathologically, there was a significant difference (p=0.037) between two groups. CONCLUSION: The N-acetylcysteine was able to decrease renal injury induced by skeletal muscle ischemia reperfusion in rats.